SME organisational challenges related to new product launch communications: The case of Inspection Technologies Ltd - Ascione, Laura (2017)
For many companies, being able to continuously develop new products and launch them into the market successfully is vital to their survival. Managing to communicate a new product to the market is an integral part of the new product launch process and will therefore largely contribute to the success of a new product launch. However, communicating a new product for launch can be a challenge for SMEs. SMEs are faced with many organisational challenges which can affect the new product launch communication strategy. This project provides a case study of the organisational challenges an SME faces and how this will affect the launch communication strategy for the launch of its upcoming new product. The company used for the case study is known as Inspection Technologies Limited. A case study was chosen as multiple types of evidence can be used when analysing the data and can best answer the exploratory nature of the research questions proposed in this project. Results from the case study allowed for two main organisational challenges to emerge: resource constraints and the informal nature of the SME. These challenges were shown to negatively affect the new product launch communication strategy. Managerial recommendations have also been given to advise Inspection Technologies how best to communicate their new product for launch in light of the organisational challenges they face.